Collaborative Creation of a Lab Rubric - Carrie Miller-DeBoer (American Society for Microbiology, 2011)
While there are a number of tested rubrics in circulation, our task was to intervene in a particular situation: the lead professor was concerned because her graduate teaching assistants held negative views about student performance on the lab reports. GTAs found poor products frustrating, and admitted that their grading was thus superficial and provided no feedback to students. Specifically, GTAs did not feel equipped to evaluate writing and, as a result, simply graded on steps completed in the lab process. We have a rubric now for an Introduction to Zoology lab that could be submitted here as a pretty darn good rubric for other instructors to use. But the intent of our “Tips and Tools” is to describe the actual creation of the rubric. We believe the active “real time” development of the rubric carried as much or more value than the finished product.